Alternative blends of CO2 for transcritical refrigeration systems. Experimental approach and energy analysis. (1st March 2023) - Sánchez, D.; Vidan-Falomir, F.; Nebot-Andrés, L.; Llopis, R.; Cabello, R.
Highlights: CO2 / R 32 (78/22%w) blend reduces the energy consumption of pure CO2 up to 17.2%. CO2 /R1270 (92.5/7.5%w) blend reduces the energy consumption of pure CO2 up to 15.7%. Both blends perform closets to a pure R1270 system and better than a pure R134a system. Abstract: As a natural refrigerant, Carbon Dioxide (CO2 ) has been extended in almost all refrigeration fields due to its environmental friendliness, high availability, and high technological development in the main components of the cycle. However, despite the benefits, CO2 is limited to high-capacity applications due to the cost of components and the complex cycle arrangements to overcome the low coefficient of performance (COP) at high ambient temperatures. A simple but effective method to solve this issue involves mixing CO2 with other refrigerants obtaining a new refrigerant mixture with higher critical points, lower working pressures and low global warming potential (GWP). Depending on the mixture percentage, the mixture flammability can be suppressed, and the performance of the refrigeration plant can be increased. Building on this, this work determines theoretically different CO2 based zeotropic blends as an alternative to pure CO2 with the restrictions of non-flammability, GWP below 150 and higher COP than pure CO2 . The results suggest two blends of CO2 /R1270 and CO2 / R 32 that have been prepared and energetically tested in a vertical display cooler using pure CO2 as a reference. The results revealed that CO2 -blends reduce energy consumption by up to 17.2 % at the ambient temperature of 25 °C and up to 12.2 % at 30 °C. Moreover, the results with CO2 -blends were closest to those obtained with pure R1270 and better than R134a under the same operating conditions.